ASEAN, institutions and democracy : the sources of adoption of the ASEAN Charter - Andrew Wiguna Mantong (2013)
This dissertation is focusing on a certain process in Southeast Asian states regional endeavour to be more integrated under the plan to establish ASEAN community: the making of ASEAN Charter. It seeks to explain how the progressive initiatives launched within the drafting process are watered-down in the Charter as the result of past legacy and choices made by states which is situated in the development of ASEAN as an institution over time. Using historical institutionalism to interpret ASEAN history and its legacy in the Charter, this dissertation would argue that path dependency predicated since the formative moments of ASEAN is reflected in the Charter on its gap between novel goals and existing institutional mechanism.